2007
DOI: 10.1007/s11214-007-9193-3
|View full text |Cite
|
Sign up to set email alerts
|

Conversations on the Habitability of Worlds: The Importance of Volatiles

Abstract: Our scientific forefathers discuss the interrelationships between water, climate, the atmosphere, and life on Earth and other terrestrial planets at a workshop in Nichtchâtel, Switzerland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 200 publications
(189 reference statements)
0
3
0
Order By: Relevance
“…Studies since the time of the Magellan mission have shown that subductive style plate tectonics do not presently exist on Venus to give it a substantial sink like that on Earth, even if there may be other types of tectonic activity allowing sinks of unquantified magnitude [e.g., Elkins‐Tanton et al ., ]. So while this work demonstrates that it may have been possible to have a moderate climate on Venus on short time scales compared with Earth [ Sleep and Zahnle , ; Bertaux et al ., ], we must wait until future data help us better constrain that planet's ancient geologic history to understand if it was capable of long‐term stable habitable climates. Other anticipated spacecraft measurements will reduce current large uncertainties in the geologic and atmospheric history of Venus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies since the time of the Magellan mission have shown that subductive style plate tectonics do not presently exist on Venus to give it a substantial sink like that on Earth, even if there may be other types of tectonic activity allowing sinks of unquantified magnitude [e.g., Elkins‐Tanton et al ., ]. So while this work demonstrates that it may have been possible to have a moderate climate on Venus on short time scales compared with Earth [ Sleep and Zahnle , ; Bertaux et al ., ], we must wait until future data help us better constrain that planet's ancient geologic history to understand if it was capable of long‐term stable habitable climates. Other anticipated spacecraft measurements will reduce current large uncertainties in the geologic and atmospheric history of Venus.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the H 2 S/SO 2 ratio provides additional information on the temperature and water content of an outgassing event, as it is governed by a redox reaction in which a lower temperature and higher water content favours the production of H 2 S from SO 2 (Oppenheimer et al 2011; and references therein). Finally, H 2 S is, in itself, a gas that is produced biotically on Earth through the metabolism of sulphate ions in acidic environments (Bertaux et al 2007), which could hypothetically be produced by micro-organisms living in sulphate deposits on Mars.…”
Section: H 2 Smentioning
confidence: 99%
“…Secondly, the H 2 S/SO 2 ratio provides additional information on the temperature and water content of an outgassing event, as it is governed by a redox reaction in which a lower temperature and higher water content favours the production of H 2 S from SO 2 (Oppenheimer et al 2011;and references therein). Finally, H 2 S is, in itself, a gas that is produced biotically on Earth through the metabolism of sulphate ions in acidic environments (Bertaux et al 2007), which could hypothetically be produced by micro-organisms living in sulphate deposits on Mars. Fig.…”
Section: H 2 Smentioning
confidence: 99%